Cover Image. Issue 4 (7th April 2022) - Cao, Jinwei; Liang, Fei; Li, Huayang; Li, Xin; Fan, Youjun; Hu, Chao; Yu, Jing; Xu, Jin; Yin, Yiming; Li, Fali; Xu, Dan; Feng, Hanfang; et al.
Abstract: This cover image is a newly created graphic that contains the material's design and applications. The nano‐liquid metal (LM)‐based highly robust stretchable electrode (NHSE) is equipped on a snowboarder for real‐time ECG monitoring (for health), conformable heating (against cold environment), and on‐cloth human‐machine interactions (for intelligent control). The zoom‐in structure of the NHSE before (right) and after (left) activation is composited in a Tai Ji Diagram to present the adaptiveness and robustness of the NHSE. (DOI: 10.1002/inf2.12302 ) Abstract : This cover image is a newly created graphic that contains the material's design and applications. The nano‐liquid metal (LM)‐based highly robust stretchable electrode (NHSE) is equipped on a snowboarder for real‐time ECG monitoring (for health), conformable heating (against cold environment), and on‐cloth human‐machine interactions (for intelligent control). The zoom‐in structure of the NHSE before (right) and after (left) activation is composited in a Tai Ji Diagram to present the adaptiveness and robustness of the NHSE. (DOI: 10.1002/inf2.12302 )